LATIHAN OTOT LENGAN TERHADAP KONDISI FISIK SISWA ATLIT PANAHAN - Ratno Susanto; Erick Burhaein; Achmad Afandi (Jayabama: Jurnal Peminat Olahraga, 2023)
This research aims to explain the effect of arm muscle training in improving the physical condition of student archery athletes, Gondanglegi District, Malang Regency. Archery, as a traditional Indonesian form of concentration science, has typical techniques taught such as preparing the right stance, placing the arrow on the bow, holding the bow string, pulling the bow, aiming at the target, releasing the shot. The research design used was a pre-experimental design with one group in a pretest-posttest design. The analysis results from the pretest and posttest are used to evaluate the effect of training. The research population was 11 student archery athletes in Gondanglegi, Malang Regency, aged 10-12 years. A sample of 11 students was carried out within 6 weeks in the Ketawang Gondanglegi field, Malang Regency. Data generated from the pretest and posttest show the mean, median, and mode for students' age, height, and weight. The majority of students had a moderate level of physical fitness on the pretest, and the majority achieved a very good level of fitness with scores on the posttest. The results of statistical analysis show that arm muscle training has a significant impact on improving the physical condition of archery student athletes. The homogeneity test results show homogeneous data variations, and there are significant differences in the paired sample t-test between the pretest and posttest scores. Arm muscle training can make a significant contribution to improving students' physical condition and concentration endurance.